The Relationship Between Insomnia And Fitness Level In Medical Faculty Students Of Universitas Muhammadiyah Purwokerto - Yulia, Nisa; Ardianto, Dony; Purbowati, Mustika Ratnaningsih; Deskianditya, Resa Budi (Herb-Medicine Journal: Terbitan Berkala Ilmiah Herbal, Kedokteran dan Kesehatan, 2024)
Physical fitness is a condition in which a person can carry out daily activities in a healthy and fit condition without quickly experiencing fatigue. Several factors can affect fitness level, such as a decrease in the hormone melatonin caused by insomnia. It will affect circadian rhythms and reduce a person’s physical activity, thus affecting fitness level. To observe the relationship between insomnia and fitness level in Medical Faculty students of Universitas Muhammadiyah Purwokerto. This study used a cross-sectional analytic observational study design. Primary data was obtained from the results of the Harvard Step Test and the Insomnia Severity Index (ISI) questionnaire. The subjects were selected through a non-probability sampling technique by purposive sampling. The statistical tests used were Fisher’s test and logistic regression. The result is 42 male students were selected from all Medical Faculty students of Universitas Muhammadiyah Purwokerto. The bivariate analysis showed that the percentage of non-insomnia respondents with poor fitness level was 73.9% and those with good fitness level was 26.1%. While the percentage of insomnia respondents with poor fitness level is 84.2% and those with good fitness level is 15.8%. Fisher’s analysis results showed a p-value 0.477 (p>0.05). There is no relationship between insomnia and fitness level in Medical Faculty students of Universitas Muhammadiyah Purwokerto.